A cultural approach to brand equity: the role of brand mianzi and brand popularity in China - Filieri, Raffaele; Lin, Zhibin; D’Antone, Simona; Chatzopoulou, Elena (The journal of brand management, 2019)
International marketers face a challenge in applying Western-derived theory in emerging markets such as China where there has been rapid economic growth and sociocultural transition. This study develops “culturally contextualized” determinants of brand equity in China. A qualitative approach consisting of 30 interviews revealed two new factors linking to brand equity: brand popularity and brand mianzi . A quantitative questionnaire survey with a sample of 321 Chinese smartphone users was conducted to test the hypotheses. The quantitative study’s findings further revealed that brand popularity and country of origin image affect brand loyalty, brand awareness, perceived quality, and brand mianzi . Additionally, the effects of brand popularity and country of origin image on brand equity were mediated by the four determinants. Finally, brand mianzi was found to be the second most important determinant of brand equity after brand loyalty, highlighting the importance of cultural factors in branding activities in emerging markets.